Pengaruh Brand Ambassador Lee Min Ho Terhadap Brand Image Azarine Cosmetic - Octaviani, Cindy; Purnawan, Ni Luh Ramaswati; Gelgel, Ni Made Ras Amanda (E-Jurnal Medium, 2024)
Azarine Cosmetic is a local brand skincare that was established in 2002 from Sidoarjo, East Java. Azarine Cosmetic appointed Lee Min Ho, an actress from South Korea, as their Brand Ambassador to promote its products to reach the market more widely and made a good image. The final of this study is to describe the influence of Brand Ambassador Lee Min Ho affect to Brand Image Azarine Cosmetic. This study using S-O-R theories as well as explanative quantitative methods by survey and measuring up to 70 respondents. The data analysis using simple linear regression analysis with SPSS 26. The result shows the impact of Brand Ambassador Lee Min Ho's affect Brand Image Azarine Cosmetic at 40%. There is a significant influence between a Brand Ambassador Lee Min Ho and the Brand Image Azarine Cosmetic.